Developments in immunosuppression - Viklicky, Ondrej; Slatinska, Janka; Novotny, Marek; Hruba, Petra (Current opinion in organ transplantation, 2021)
PURPOSE OF REVIEW: In this review, we discuss achievements in immunosuppression in kidney transplant recipients published at last 18 months. RECENT FINDINGS: Results of recent trials with everolimus in low-risk primary kidney transplant recipients suggest that lowTAC/EVR combination is noninferior and CMV and BKV viral infections are less frequent to standTAC/MPA. Iscalimab monoclonal antibody, which prevents CD40 to CD154 binding, has just recently entered phase II clinical studies in kidney transplantation. Eculizumab, anti-C5 monoclonal antobody was recently shown to improve outcomes in DSA+ living-donor kidney transplant recipients requiring pretransplant desensitization because of crossmatch positivity. Proximal complement C1 inhibition in patients with antibody-mediated rejection was studied in several phase I trials. SUMMARY: Recent knowledge creates a path towards future immunosuppression success in sensitized recipients and in those in high risk of viral infections or CNI nephrotoxicity.
Keywords: Randomized Controlled Trials as Topic; rejekce štěpu; Graft Rejection; Everolimus; Antibodies, Monoclonal; lidé; Transplant Recipients; Immunosuppressive Agents; everolimus; transplantace ledvin; příjemce transplantátu; Kidney Transplantation; Immunosuppression Therapy; randomizované kontrolované studie jako téma; monoklonální protilátky; humanizované monoklonální protilátky; Antibodies, Monoclonal, Humanized; imunosupresivní léčba; imunosupresiva; Humans